2014
DOI: 10.1186/1744-9081-10-38
|View full text |Cite
|
Sign up to set email alerts
|

Colour vision in ADHD: Part 1 - Testing the retinal dopaminergic hypothesis

Abstract: ObjectivesTo test the retinal dopaminergic hypothesis, which posits deficient blue color perception in ADHD, resulting from hypofunctioning CNS and retinal dopamine, to which blue cones are exquisitely sensitive. Also, purported sex differences in red color perception were explored.Methods30 young adults diagnosed with ADHD and 30 healthy young adults, matched on age and gender, performed a psychophysical task to measure blue and red color saturation and contrast discrimination ability. Visual function measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 60 publications
(71 reference statements)
0
24
0
Order By: Relevance
“…We defined a perceptual error as a press of the wrong button among the 2 relevant ones. We optimized the quantitative characterization of perceptual function by: a) using simple stimuli with feature dimensions orientation and color, thus minimizing high-level cognitive effects; b) varying stimuli parametrically along a continuum to estimate psychometric curve parameters (standard in perceptual psychophysics but still relatively rare in the study of ADHD [5,36,37,39,41,42]); c) using an efficient stimulus selection method to minimize the number of trials needed for accurate estimation of parameters [43]. Broadly, our work follows a recent proposal to apply four levels of analysis to computational psychiatry: development of behavioral tasks, fitting of computational models, estimating parameters, and classification for diagnosis [44].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We defined a perceptual error as a press of the wrong button among the 2 relevant ones. We optimized the quantitative characterization of perceptual function by: a) using simple stimuli with feature dimensions orientation and color, thus minimizing high-level cognitive effects; b) varying stimuli parametrically along a continuum to estimate psychometric curve parameters (standard in perceptual psychophysics but still relatively rare in the study of ADHD [5,36,37,39,41,42]); c) using an efficient stimulus selection method to minimize the number of trials needed for accurate estimation of parameters [43]. Broadly, our work follows a recent proposal to apply four levels of analysis to computational psychiatry: development of behavioral tasks, fitting of computational models, estimating parameters, and classification for diagnosis [44].…”
Section: Introductionmentioning
confidence: 99%
“…To respond, the participant could press any one of 8 keys but only 2 were task-relevant on a given trial. [38][39][40][41] or cross-modal switching [42], or more complex forms of task would produce larger di↵erences on a TIMO-like executive function measure.…”
Section: Introductionmentioning
confidence: 99%
“…While Bartgis et al (2009) utilized the Functional Acuity Contrast Test (FACT; Ginsburg 1998), Kim et al (2015) used the Pelli-Robson Contrast Sensitivity Test (Pelli et al 1988) and Stevens et al (2012) used a test they designed specifically for this study. Kim et al (2014a) did not find any significant differences between adults with ADHD and NCs in performance on a contrast discrimination task, where participants had to decide which stimulus out of two (sinusoidal gratings) ''looks higher in contrast''. Our calculated Cohen's d for the difference in contrast discrimination between men with ADHD and men in the NC group was found to be small (d = 0.21), whereas the Cohen's d for the differences between women with and without ADHD was found to be of medium size (d = 0.63).…”
Section: Visual Perceptionmentioning
confidence: 60%
“…In combination with the medium effect size found for differences between females with ADHD and NCs, it may be that this test was underpowered. Kim et al (2014a) also investigated color saturation discrimination which is the ability to discriminate between different intensities of a specific hue and found that females with ADHD had significantly reduced color saturation discrimination compared to females of the NC group, with large effect sizes; Cohen's d ranged from 0.85 to 1.01 (Kim et al 2014a). Males with ADHD did not differ significantly from their male peers.…”
Section: Visual Perceptionmentioning
confidence: 99%
See 1 more Smart Citation